Occurrence of marine biotoxins and shellfish poisoning events and their causative organisms in argentine marine waters - Krock, Bernd (2018)
In the Argentine Sea, marine phycotoxins of microalgal origin associatedwith five shellfish poisoning syndromes have been reported. The most problematic interms of toxicity and geographic distribution is paralytic shellfish poisoning (PSP), followedby diarrhetic shellfish poisoning (DSP). In contrast, amnesic shellfish poisoning(ASP), spiroimine shellfish poisoning (SSP), and azaspiracid shellfish poisoning (AZP)have not been reported to cause human illness or closures of shellfish harvest sites inArgentina to date but pose a potential risk, as associated toxins and producing organismsare present in Southwest Atlantic waters and were detected at subregulatory levelsin mollusks. Alexandrium catenella and Gymnodinium catenatum have been identifiedas producers of the PSP toxins C1/2, gonyautoxins (GTX1-4), saxitoxin (STX),and neosaxitoxin (NEO) in the Argentine Sea. Nine potentially toxigenic species ofthe diatom genus Pseudo-nitzschia have been reported for Argentinean coastal waters:P. australis, P. brasiliana, P. delicatissima, P. fraudulenta, P. multiseries, P. pseudodelicatissima,P. pungens, P. seriata, and P. turgidula, all of which are known to produce theneurotoxin domoic acid that causes ASP. Two genera have been identified as producersof DSP toxins in Argentina: the benthic dinoflagellate Prorocentrum lima and severalspecies of the pelagic dinoflagellate genus Dinophysis: D. acuminata, D. caudata,D. fortii, D. norvegica, and D. tripos. The occurrence of these species in Argentine watersis associated with okadaic acid (OA), dinophysistoxin-1 (DTX-1), pectenotoxin-2(PTX-2), and pectenotoxin-2 seco acid (PTX-2sa). Historically, yessotoxins (YTXs)were also included in DSP syndrome and all three known YTX-producers have beenconfirmed in Argentinean waters: Gonyaulax spinifera, Lingulodinium polyedra, andProtoceratium reticulatum, but of these only P. reticulatum could be associated with YTXproduction to date. Several species of the family Amphidomataceae, which cause AZP,have been reported for Argentina: Amphidoma languida, Azadinium dexteroporum,Az. luciferelloides, Az. poporum, and Az. spinosum. In Argentinean coastal waters, outof these species only Az. poporum has been identified as toxigenic to date, as it producesazaspiracid-2 (AZA-2) and its phosphorylated form. Currently in Argentina, seafood ismonitored for the risk of ASP, AZP, DSP, and PSP.